Physicochemical Properties of Soil Cultivated with Durian (Durio zibethinus Murr.) in Gua Musang, Kelantan - Athirah Amran; Mohd Rizal Ariffin; Isharudin Md Isa; Osumanu Haruna Ahmed; Gary Herman; Siti Hazwani Muhamad; Nur Atikah Mohd Nor; Mohd Nizar Khairuddin (AGRIVITA, Journal of Agricultural Science, 2023)
This study was carried out in an area cultivated with durian in Gua Musang, Kelantan with a soil series of Rengam-Jerangau. The objective of this study was to determine the physicochemical properties of soil cultivated with durian at different elevations and samplings. The soil composite sampling was determined at three elevations (top, middle and bottom elevation) marked using GPS coordinate with two different depths (0-15 cm and 15-30 cm). The United States Department of Agriculture (USDA) of the soil texture is clay with bulk density ranging between 0.98 to 1.11 g/cm3. Significant parameters at alpha value of 95% include total carbon content (0.903% until 1.389%), total sulphur content (0.059% to 0.100%), exchangeable bases calcium, potassium and sodium at 3.520 cmolc/kg to 5.582 cmolc/kg, 0.380 to 0.581 cmolc/kg and 0.101 to 0.155 cmolc/kg respectively. From the significant parameters, only exchangeable potassium was affected by the by both elevation and depth of the sampling while the other parameters were only affected by the elevation. As some of the nutrients had been classified as low, extensive measures need to be done for healthy growth performance.